2021
DOI: 10.1111/cge.14040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variability of neurofibromatosis 1: A modifying role of cooccurring PTPN11 variants and atypical brain MRI findings

Abstract: Neurofibromatosis 1 (NF1) is a disorder characterized by variable expressivity caused by loss-of-function variants in NF1, encoding neurofibromin, a protein negatively controlling RAS signaling. We evaluated whether concurrent variation in proteins functionally linked to neurofibromin contribute to the variable expressivity of NF1. Parallel sequencing of a RASopathy gene panel in 138 individuals with molecularly confirmed clinical diagnosis of NF1 identified missense variants in PTPN11, encoding SHP2, a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…NF1 is characterized by an extremely variable clinical spectrum, ranging from isolated skin manifestations to a more complex multi-system involvement, and approximately 10% of individuals with NF1 share phenotypic features with Noonan syndrome, a RASopathy caused in about half of patients by mutations in PTPN11 [16,26,27]. This was the case with patient 8, who carried an activating PTPN11 variant together with a loss-of-function NF1 variant, resulting in typical NF1 skin findings associated with a severe NF1 neuroradiological phenotype, peculiar cortical hyperintensities and Noonan-like features [16]. Moreover, during follow-up, she developed severe hypostaturalism of mixed etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF1 is characterized by an extremely variable clinical spectrum, ranging from isolated skin manifestations to a more complex multi-system involvement, and approximately 10% of individuals with NF1 share phenotypic features with Noonan syndrome, a RASopathy caused in about half of patients by mutations in PTPN11 [16,26,27]. This was the case with patient 8, who carried an activating PTPN11 variant together with a loss-of-function NF1 variant, resulting in typical NF1 skin findings associated with a severe NF1 neuroradiological phenotype, peculiar cortical hyperintensities and Noonan-like features [16]. Moreover, during follow-up, she developed severe hypostaturalism of mixed etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients had NF1-related OPGs. Patient 8, who has already been described, was affected by NF1 and, in addition, carried a PTPN11 mutation [16]. Children with NF1-related OPG were significantly older than sporadic cases (median (range) age in months: 21.2 (range 14-26) versus 10 (range 3-17); p = 0.015).…”
Section: Clinical Features At Diagnosismentioning
confidence: 92%
“…Recently, using a systems biology strategy, Kowalski et al ( 38 ) identified 10 candidate modifier genes related to the NF-1 phenotype, namely AKT1, BRAF, EGFR, LIMK1, PAK1, PTEN, RAF1, SDC2, SMARCA4 , and VCP . What's more, D'Amico et al ( 39 ) identified that gain-of-function and hypomorphic variants in PTPN11 , a positive regulator of RAS, have been shown to worsen and mitigate, respectively, the severity of the NF1 phenotype. Besides, the allelic heterogeneity of constitutional NF1 mutations, environmental factors may also be associated with phenotypic variability ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likely due to its high prevalence, NF1 has been associated with other genetic conditions that can complicate the phenotype of patients, although the main features of NF1 remain well recognizable and preserved. NF1 association with Noonan syndrome (PTPN11) [119,120], Huntington's disease (HTT) [121], congenital myopathy (RYR1) [122], hereditary breast cancer (BRCA1) [123], multiple endocrine neoplasia type 2 (RET) [124], and Jalili syndrome (association between conical rod-dystrophy and amelogenesis imperfecta) are all described [125]. Down syndrome and NF1 were also observed together, as well as a pathogenic de novo variant of NF1 and de novo deletion of chromosome 20q11.23 [126,127].…”
Section: Association With Other Genetic Disordersmentioning
confidence: 99%